POLYSUBSTANCE USE IN INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Bogale, Kaleb; Vrana, Kent; Raup-Konsavage, Wesley; Walter, Vonn; Stuart, August; Dalessio, Shannon; Koltun, Walter; Bernasko, Nana; Tinsley, Andrew; Williams, Emmanuelle; Clarke, Kofi; Coates, Matthew
Abstract: Background: Polysubstance Use (PSU), the use of two or more substances of abuse, has been associated with increased risk for development of psychiatric conditions and early death compared to both monosubstance use or no substance use. The vast majority of clinical research on prescription or recreational drug consumption in patients with inflammatory bowel disease (IBD), including both Crohn's disease (CD) and ulcerative colitis (UC), has focused on use of individual substances. We evaluated the incidence and impact of PSU in IBD and assessed potential predisposing factors in this setting. Methods: We performed a retrospective analysis using a consented IBD natural history registry from a single tertiary care referral center between 1/1/2015–8/31/2019. Demographics, endoscopic severity (using Mayo endoscopy sub-score for UC and Simple Endoscopic Score for CD), totals and sub-scores of surveys (Harvey-Bradshaw Index, Simple Clinical Colitis Activity Index, Hospital Anxiety and Depression Scale, Short IBD Questionnaire) assessing for symptoms (abdominal pain, fatigue, anxiety/depression, gas, diarrhea, rectal bleeding, and fecal urgency), substance use (tobacco, alcohol, marijuana, cocaine, methamphetamine, heroin, opiates, or benzodiazepine), and antidepressant or anxiolytic medication were abstracted. PSU was defined as concurrent use of two or more non-prescription drugs or substances, and healthcare resource utilization was defined as any IBD-related imaging, emergency room visit, hospitalization, or surgery over the prior 12 months. We computed descriptive statistics and performed contingency table analyses in order to identify associations between PSU and a variety of demographic and clinical characteristics. Multivariable logistic regression models were fit incorporating the clinical factors described above. Results: 315 consecutively enrolled IBD patients (166f:149m; 214 CD and 101 UC) were included. Sixty-six patients (21.0%) were polysubstance users. Of these patients, 40.9% had moderate to severe disease activity, 47.0% had extra-intestinal manifestations (EIM), and 36.4% demonstrated an anxious or depressed state. EIM and antidepressant or anxiolytic use were positively associated with PSU on bivariate analysis (Table 1) and multivariable analysis (Table 2). Conclusions: PSU is common in IBD, including both CD and UC. Interestingly, disease activity, IBD therapy type, and IBD-related symptoms were not associated with PSU. EIM and antidepressant or anxiolytic use were the only statistically significant predictors of PSU among patients with IBD in the multivariable logistic regression models. Our study represents the first evaluation of PSU within IBD and reinforces the importance of appropriate substance use screening among IBD patients, particularly among those with EIM and antidepressant or anxiolytic use.